A Novel Nanomicellar Combination of Fenretinide and Lenalidomide Shows Marked Antitumor Activity in a Neuroblastoma Xenograft Model - Orienti I; Nguyen F; Guan P; Kolla V; Calonghi N; Farruggia G; Chorny M; Brodeur GM (Dove Medical Press, 2019)
Isabella Orienti,1 Ferro Nguyen,2 Peng Guan,2 Venkatadri Kolla,2 Natalia Calonghi,1 Giovanna Farruggia,1 Michael Chorny,2 Garrett M Brodeur2 1Department of Pharmacy and Biotechnology, University of Bologna, Bologna 40127, Italy; 2Divisions of Oncology, Children’s Hospital of Philadelphia, Philadelphia, PA 19104, USACorrespondence: Isabella Orienti Email isabella.orienti@unibo.itPurpose: Currently >50% of high-risk neuroblastoma (NB) patients, despite intensive therapy and initial partial or complete response, develop recurrent NB due to the persistence of minimal residual disease (MRD) that is resistant to conventional antitumor drugs. Indeed, their low therapeutic index prevents drug-dose escalation and protracted administration schedules, as would be required for MRD treatment. Thus, more effective and less toxic therapies are urgently needed for the management of MRD. To address this aim, we evaluated a new combination of fenretinide and lenalidomide, both endowed with antitumor activity and low-toxicity profiles. New nanomicelles were prepared as carriers for this combination to maximize bioavailability and accumulation at the tumor site because of the enhanced permeability and retention (EPR) effect.Experimental design: New nanomicelles containing the fenretinide–lenalidomide combination (FLnMs) were prepared by a one-step method, providing high drug encapsulation and micelle dimensions suitable for tumor accumulation. Their administration to mice bearing human NB xenografts allowed us to evaluate their efficacy in comparison with the nanomicelles containing fenretinide alone (FnMs).Results: Treatment by FLnMs significantly decreased the tumor growth of NB xenografts. FLnMs were more active than FnMs despite comparable fenretinide concentrations in tumors, and lenalidomide alone did not show cytotoxic activity in vitro against NB cells. The tumor mass at the end of treatment with FLnMs was predominantly necrotic, with a decreased Ki-67 proliferation index.Conclusion: FLnMs provided superior antitumor efficacy in NB xenografts compared to FnMs. The enhanced efficacy of the combination was likely due to the antiangiogenic effect of lenalidomide added to the cytotoxic effect of fenretinide. This new nanomicellar combination is characterized by a low-toxicity profile and offers a novel therapeutic option for the treatment of high-risk tumors where the persistence of MRD requires repeated administrations of therapeutic agents over long periods of time to avoid recurrent disease.Keywords: neuroblastoma, drugs combination, nanomicelles, fenretinide, lenalidomide